Perbandingan Aktivitas Antioksidan Ekstrak Etil Asetat, N-Heksana dan Metanil dari Daun Hantap (Sterculia oblongata R.Br) - Rais Syifa Aristianto; Nitya Nurul Fadilah; Susanti (Universitas Airlangga, 2026)
Degenerative diseases are chronic health conditions characterized by a gradual decline in organ function, often triggered by high levels of environmental pollutants and the accumulation of free radicals. Free radical activity can cause cellular and tissue damage, contributing to the development of various degenerative diseases such as diabetes, cancer, inflammation, immune disorders, premature aging, and cardiovascular diseases. This study aims to evaluate the antioxidant activity of Sterculia oblongata R.Br leaf extracts based on the polarity of the extraction solvents used. The extraction process was carried out through graded maceration using ethyl acetate, n-hexane, and ethanol. Antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method with UV-Vis spectrophotometry to determine the IC₅₀ values of each extract. The results showed that the ethyl acetate extract exhibited the strongest antioxidant activity, with an IC₅₀ value of 17.33 µg/mL, followed by the ethanol extract (19.10 µg/mL) and the n-hexane extract (23.97 µg/mL). Based on the antioxidant activity classification, all three Sterculia oblongata leaf extracts demonstrated very strong antioxidant activity. These findings also indicate that higher solvent polarity corresponds to increased antioxidant activity. Keywords: Antioxydant, Sterculia oblongata Leaves, Polarity, Solvent